Satisfaction of goals attainment and intention to restructure among Malaysian SME entrepreneurs - Mohd Hizam Hanafiah; Sh. Usman Yousaf; Zizah Che Senik (2016)
Entrepreneurs’ future directions such as intention to restructure may serve as an important indicator in ensuring sustainability and growth of entrepreneurial businesses. Based on the theoretical foundation of Entrepreneur’s Goals Attainment Theory, this research empirically investigates the influence of personal goals attainment on entrepreneurs’ intentions to restructure. Self-administered questionnaires were used to collect data from 285 conveniently selected Malaysian SME entrepreneurs. The Hierarchical Multiple Regression Analyses of data show that entrepreneurs’ attainment of intrinsic rewards, economic gains, goals, and level of education are significant and positively related to their intention to restructure. In contrast, it is found that the attainment of perceived autonomy goals and family goals do not have a relationship with the entrepreneurs’ intentions to restructure their businesses. The concluding part of this paper presents the study’s implications along with limitations and several future recommendations.